Food Safety Knowledge, Attitudes and Practices Of Fish Handlers in Kirinyaga County Markets, Kenya - Kyule, Domitila Ndinda; Mburu, Saimon Wambui; Munguti, Jonathan; Obiero, Kevin; Abwao, Jacob; Ndegwa, Daniel; Outa, Nicholas; Ogello, Erick (My University, 2023)
Fish and fish products have high nutritional value and are important in supplementing human diet. Fish products have little or no cholesterol and saturated fat, but instead have omega 3 and low-fat content essential for human health. Despite the high nutritional value of fish products, their consumption is hindered significantly by setbacks such as spoilage and foodborne diseases that spread through contamination in the fish supply chain. The objective of this study was to evaluate fish vendors' attitudes, knowledge, and practices on food safety in selected markets in Kirinyaga County that included Sagana, Tebere, Mwea, Ndia, Kianyaga, and Kerugoya markets. A structured questionnaire was administered to 54 fish vendors to collect information on fish safety, spoilage, risk factors, personal hygiene, food contamination, type of hazards, foodborne diseases and attitudes towards training on food safety. Statistical Package for Social Sciences (SPSS) version 22.0 was used to analyze the data from the respondents. The relationship between fish vendors’ demographic characteristics and risk factors was assessed using Spearman’s rank correlation coefficient. The majority of the fish vendors had a positive attitude towards education in hygiene practices (56%). There was a positive correlation between education and fish vendors' awareness of fish foodborne diseases at p<0.05. The study revealed that fish foodborne diseases awareness was positively influenced by respondents' level of experience and age. Moreover, there was also a significant (p˂ 0.05) positive correlation on the awareness of fish foodborne diseases with hygiene and food safety. Majority of the fish handlers had average level of knowledge, attitude and hygiene practices for food safety. These findings presented a foundation for formulating policies to increase food safety and hygiene practices of fish handlers in the region, thereby preventing foodborne diseases and postharvest losses. The results of this study can also form a basis for an in-depth research for students and researchers in various disciplines such as public health, marketing, community development and more.
Keywords: Food Safety; Food Products; Foodborne Diseases